The seventh century in the West-Syrian chronicles - Palmer, Andrew N., 1955-; Palmer, Andrew N., 1955-; Palmer, Andrew N., 1955-; Brock, Sebastian P., 1938-; Brock, Sebastian P., 1938-; Brock, Sebastian P., 1938-; Hoyland, Robert G., 1966- (Translated texts for historians ;, 1993)
The Seventh Century in the West-Syrian Chronicles makes accessible to a wide public sources vital for the reconstruction of events in the first Islamic century, covering the period which ends with the unsuccessful Arab siege of Constantinople, an event which both modern historians and Syriac chronographers see as making a decisive caesura in history. The general introduction enables a newcomer to the field to establish his bearings before tackling the texts.